To Alleviate or Elevate the Euroamerican Genealogy Fever - Iain Riddell (Genealogy, 2018)
There has been a quiet cultural drift towards professionalism in genealogy over the last two decades. Developments in the UK on this subject have resulted in educational offerings that support professionalism through accountability to service consumers while a US debate has pushed for a recognised and regarded scholarship to underpin the professional genealogist. This article places the educational and learning needs of three broad groups of genealogists into the framework of the professional debate in its generality and genealogical specifics. With a concentration on the British context, the article considers the cultural–commercial signals and support offered to ‘armchair enthusiasts’; the emerging models of professional education and formation aimed at lineage makers and the ongoing fractured models of scholastic genealogy. Looking ahead at educational needs, genealogy like other professions is now under threat from advances in artificial intelligence and algorithms, which could slice through the underpinnings of genealogical professionalism. The article concludes with a discussion of an alternative approach to genealogical education derived from the proposition that professionalism is to be found in the outputs and outcomes rather than the organisation of the practitioners of economic activity. From this stance, the needs of a full range of people pursuing genealogy can be addressed and their work informed by the developing understanding of Euroamerican kinship.